Policy Advocacy for Disaster Risk Reduction Integration in Regional Spatial Planning: Lessons from Purwakarta - Rafita, Afi; Ningrum, Sinta; Sukarno, Dedi (Journal of Public Representative and Society Provision, 2025)
This study investigates policy advocacy strategies employed to integrate disaster risk reduction (DRR) into spatial planning through a case study of the revised Spatial Plan (RTRW) of Purwakarta Regency for 2025–2045. Given Indonesia’s high disaster risk profile, integrating DRR into planning documents is crucial to ensuring sustainable and resilient regional development. Despite national regulatory mandates, the previous RTRW of Purwakarta (2011–2031) inadequately addressed disaster vulnerability. This research adopts a qualitative descriptive case study design, using in-depth interviews with stakeholders from local government agencies and technical experts. The analysis is guided by the Advocacy Logic Model by Gen and Wright (2013), which outlines advocacy components including input, activities, and outcomes. The integration of DRR into the revised RTRW of Purwakarta was largely driven by a strong sense of agency among stakeholders, effective inter-agency collaboration, and the technocratic engagement of experts. Key activities involved coalition-building, engaging policymakers, public mobilization, and defensive actions to sustain reform momentum. These strategies led to a substantial shift in decision-makers' awareness, resulting in the formal incorporation of spatially explicit disaster risk data into the revised RTRW. The study concludes that strategic and context-sensitive advocacy can effectively bridge the gap between regulatory imperatives and local implementation, especially in regions facing complex disaster risks. These findings offer practical insights for policymakers and contribute theoretically to the literature on disaster governance and public policy advocacy.